The effect of establishment motives in international joint venture partner selection and performance. - Koskinen, Miika (My University, 2010)
For decades companies have used international strategies and international operations as their choice for conducting business abroad. Due to increased globalization and advanced competition companies face even more pressures to operate efficiently and at the same time internationally. However, entering into new foreign markets can be challenging, especially without a partner. Collaborative ventures provide potential solutions for companies to pursue international experience and success. International joint ventures are increasing their popularity as a suitable operation model for international expansion. Joint ventures are widely studied, yet certain research subjects lack focus. In this study the effect of establishment motives in international joint venture partner selection and performance was examined. The theoretical part of the study was constructed with previous theory regarding establishment motives, partner selection and performance affecting factors. The role and importance of different establishment motives were covered and organizational learning, trust and control were examined as performance affecting factors. Overview on the wide concept of partner selection was given and the different performance measurements of JV were explored. The theoretical framework of the study was developed further with a case study of three joint ventures established by Finnish international companies. The data was collected by sending a questionnaire with open-ended questions to the respondents. According to the results of the empirical study, the establishment motives are linked with the partner selection criteria. Companies tend to value different partner selection criteria based on their initial motives, and the specific establishment motives influence the desirable attributes of the joint venture partner. This partly implies that the linkage between establishment motives and the performance of the joint venture is indirect as the primary effect of establishment motives is on the partner selection. The role of the partner selection is notable in the performance of the joint venture, but other factors have effect on the success of the joint venture as well.
Keywords: International joint venture; establishment motives; partner selection; performance; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|